2019
DOI: 10.3390/ijms20092111
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Enhances Cell-Cell Adhesion Mediated by β1 Subunits of the Na+,K+-ATPase in CHO Fibroblasts

Abstract: Adhesion is a crucial characteristic of epithelial cells to form barriers to pathogens and toxic substances from the environment. Epithelial cells attach to each other using intercellular junctions on the lateral membrane, including tight and adherent junctions, as well as the Na+,K+-ATPase. Our group has shown that non-adherent chinese hamster ovary (CHO) cells transfected with the canine β1 subunit become adhesive, and those homotypic interactions amongst β1 subunits of the Na+,K+-ATPase occur between neighb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 88 publications
(128 reference statements)
1
16
0
Order By: Relevance
“…S3, we observed no change in fetal survival after administration of pNaKtide to female mice before mating and continued until the end of pregnancy. It is important to mention that pNaKtide has been proven to be specific and effective in blocking the NKA/Src receptor signaling in vivo (22)(23)(24)(25)(26), and our control experiments showed that pNaKtide could cross the placental barrier. Moreover, this lack of pNaKtide effect on mouse embryogenesis appears to be consistent with a previous report demonstrating that neutralization of endogenous ouabain by injection of an anti-ouabain antibody did affect the kidney development of neonatal mice but did not affect their overall survival (20).…”
Section: Inhibition Of Receptor Nka/src Complex Does Not Affect Embrymentioning
confidence: 64%
See 1 more Smart Citation
“…S3, we observed no change in fetal survival after administration of pNaKtide to female mice before mating and continued until the end of pregnancy. It is important to mention that pNaKtide has been proven to be specific and effective in blocking the NKA/Src receptor signaling in vivo (22)(23)(24)(25)(26), and our control experiments showed that pNaKtide could cross the placental barrier. Moreover, this lack of pNaKtide effect on mouse embryogenesis appears to be consistent with a previous report demonstrating that neutralization of endogenous ouabain by injection of an anti-ouabain antibody did affect the kidney development of neonatal mice but did not affect their overall survival (20).…”
Section: Inhibition Of Receptor Nka/src Complex Does Not Affect Embrymentioning
confidence: 64%
“…These findings have substantially increased our understanding of 1 NKA/Src interaction in cell biology and animal physiology. It is important to mention that several groups not associated with us have successfully used pNaKtide to block ouabain and NKA signaling in vitro and in vivo (23)(24)(25)(26)51). While our group and others continue to characterize the molecular basis and biological function of the NKA/Src receptor complex, we propound that the question of NKA/caveolin-1 interaction is a more pressing one in the context of this study.…”
Section: Discussionmentioning
confidence: 93%
“…As previously shown, transfection of canine NaK β 1 subunit in CHO fibroblast increases cell adhesion [10,35]. We performed Dispase assays to assess cell-cell adhesion in the stably transfected cell lines.…”
Section: Resultsmentioning
confidence: 98%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%